(untitled) (مجلة جامعة اللاذقية - سلسلة العلوم الصحية, 2016)
تهدف هذه الدراسة إلى معرفة تأثير الجنس على سماكة النسج الرخوة للذقن في الأنماط المختلفةلدوران الفك السفلي (أمامي- طبيعي – خلفي). تتألف العينة من 100 صورة شعاعية سيفالومترية جانبية لـ (69 أنثى _ 31 ذكر) بالغين, وقد تم انتقاؤهم وفق الشروط التالية : العمر بين 18 -26 سنة , استبعاد جميع حالات الشذوذات الاطباقية الشديدة , الإطباق دائم ولايوجود شذوذات شكلية بالأسنان دون أخذ الأرحاء الثالثة بعين الاعتبار , عدم وجود معالجة تقويمية سابقة , خلو المريض من الأمراض الجهازية أو التشوهات الخلقية, عدم وجود أي قصة جراحية سابقة في منطقة الرأس والعنق تم تقسيم العينة إلى مجموعات حسبالجنس والدوران الفكي السفلي (أمامي- طبيعي – خلفي) ثم دراسة مجموعة من المتغيرات الممثلة للدوران الفك السفلي وأخرى ممثلة لقياسات الأنسجة الخوة للذقن.وقد أظهرت النتائج اختلاف متوسطات مقاييس ثخانة الأنسجة الرخوة ومؤشرات دوران الفك السفلي بين الجنسين لصالح الذكور, كما أن المتوسطات الحسابية أظهرت ارتباطاً بين متغيرات سماكة النسج الرخوة للذقن عند الإناث مع الأنواع الثلاثة لدوران الفك السفلي مقارنةً مع الذكور. The aime of this study was to determinethe effect of gender on the soft tissue of the chin at each type of rotation patterns of the lower jaw (Anterior - normal - Posterior) The sample consisted of 100 X-ray Lateral cephalometric radiographs of (69 female _ 31 male) adults, has been selected according to the following conditions: Age between 18-26 years old, , exclusion of all cases of Intenseocclusal abnormalities , Permanentocclusionand there is noformaldentalabnormalitieswithout takinginto accountthe thirdmolars, The absence ofa previousorthodontic treatment, the patient free fromsystemic diseasesorcongenital malformationsanddevelopmentaldisordersandsyndromesand there is no story of a previous surgery in the head and neck area The sample was divided into groups according tosex andmandibularrotation(Anterior - normal - Posterior). Then we studied variablesrepresentative the lower jaw rotation andanother ones representativethemeasurementsof the chinsoft tissue. The results showed a difference theaveragesof the soft tissue thickness and the indicators of mandible rotation between the sexes In favor of males, And theaveragesof thevariables showed Correlationbetween chinsofttissuethicknessin femaleswiththree typesoflower jawrotation Compared with males